(untitled) - Mandrou, Robert (England, 1985)
Contents: A history of European thought? The general title of this series matters less, it seems to me, than the title given to this volume of the series: From Humanism to Science. For we are not here concerned with the history of ideas as it has been pursued for so long by the university philosophers and their imitators, and as it is still secretly cherished by those who are fond of sustained filiations and patiently rediscovered continuities.
Keywords: Civilization, Modern,Văn minh, hiện đại